Development factors of museology around the world (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article talks about changes in the field of museums and museology around the world, and the factors of their formation. In addition, the researches of museum scientists are studied on an evolutionary basis, and the article also contains some information about the inclusion of museology as an independent science in the field of education and training of specialists.